2019
DOI: 10.1007/s00520-019-05202-4
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment needs in hospitalized cancer patients: a retrospective cohort study

Abstract: Purpose The objectives of this study were to describe the distribution and the clinicopathological features of the most common causes for dental treatment needs during the hospitalization of cancer patients. Methods A retrospective cohort study of 2664 hospitalized cancer patients that analyzed the main dental treatment needs and dental procedures performed from January 2010 to December 2017. Results A total of 2664 medical patients were included in this study. Non-Hodgkin lymphoma (17.2%) was the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
8
0
6
Order By: Relevance
“…Investigations regarding oral health conditions in hospitalized patients have already been described. 28,29,30 Bertaud-Gounot et al, 31 evaluated the oral health status of institutionalized psychiatric patients in a hospital with free-demand dental service. Their results showed that these patients presented four times more decayed teeth than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations regarding oral health conditions in hospitalized patients have already been described. 28,29,30 Bertaud-Gounot et al, 31 evaluated the oral health status of institutionalized psychiatric patients in a hospital with free-demand dental service. Their results showed that these patients presented four times more decayed teeth than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the requirement for a specific diet like feeding tubes, narcotic analgesia, and prolonged hospitalization, oral problems linked to cancer progression or connected to oncologic treatment may also raise the overall treatment cost. 4 Oral mucositis is a painful, inflammatory, and typically ulcerative illness that can occur as a result of cancer treatment. Almost all patients having head and neck radiation therapy, as well as 75-100% of hematopoietic stem cell transplant patients, develop this disease, with higher rates linked with particular conditioning regimens.…”
Section: Introductionmentioning
confidence: 99%
“…A inovação presente no software Tasy é alavancada pela conectividade entre as diferentes áreas, alas e equipes constituintes dos serviços de saúde, integrando e unificando a base de dados em um só espaço virtualizado e que desempenha a comunicação de forma ágil e intuitiva (PHILIPS, 2017). Dessa forma, compreende-se que o software não pode ser definido somente como uma base de registro profissional, pois se incorpora a ele a relação de suporte organizacional de toda a instituição de saúde e de ensino (OLIVEIRA et al, 2020;PISSAIA, BESCHORNER, 2016).…”
Section: Introductionunclassified